MAKNA POLA IKAT PADA PROPERTI TARI JEPIN TALI PESAWAT TERBANG DI KOTA PONTIANAK - Yanto, Yanto; Fretisari, Imma; Muniir, Asfar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe research background is to find deeper meaning of the handwoven pattern on theÂ property of Jepin Dance. 1) describing the binding pattern of the Jepin Tali Pesawat Terbang dance propery, and 2) describing the meaning of the Jepin Tali Pesawat Terbang dance property. The descriptive method is used, a qualitative form was applied and using semiotics. Sources of research data are the results of interviews with Yusuf Dahyani, Juhermi Thahir, and Anwar Djafar as the interviewees who researcher got the information from, this producting dataÂ that researchers used collection of interview dan observation techniques. Data validity testing techniques include extension of observation and triangulation were applied. The tari jepin tali pesawat has 4 bonding patterns. Namely 1) A back pattern which symbolizes intertwined relationship that cannot be separated because of cooperatif in it. 2). The pattern of entangling means that in simple survival, human being must remain on the straight path by strengthening their faith and heart to get through various trials in this world. 3). The knot tied pattern means no matter how strong human, humans still have weakness inthemselves. To get what each person wants, one must strive and be patient in order to be a better person. 4). Belted pattern means that everything in the world both good and bad is all based on the will or power of the almighty God. According to the results of this study, it is suggested that people should care more and love the local traditions by preserving them so that the arts can be known especially by the local community and even the world that the tari jepin tali pesewat becomes a local cultural treasure that will not be forgotten as he timegoes by.Keywords: Meaning, Pattern, Tari Jepin Tali Pesawat.